Automatic knife sharpener / Mohamad Naqib Norlizan, Noor Hafiz Noordin and Mohd Ghazali Mohd Hamami - Norlizan, Mohamad Naqib; Noordin, Noor Hafiz; Mohd Hamami, Mohd Ghazali (School of Mechanical Engineering, 2023)
The traditional manual knife sharpening process is time-consuming and requires significant energy. Additionally, the results of the process depend on the individual's experience, leading to inconsistency. To address this issue, this study proposes the development of an automatic knife sharpener. The design and fabrication of this machine will incorporate mechanical components, such as a motor, as well as electrical parts to control the mechanism. Standard machining processes like grinding, cutting, and drilling will be employed during the fabrication. The automatic knife sharpener machine is expected to be more efficient than the traditional process in terms of time consumption and consistency of the sharpened blades. In conclusion, the automatic knife sharpener will provide added value to the sharpening process, while also ensuring safety considerations can be implemented